Intervensi Gizi Spesifik pada 1000 Hari Pertama Kehidupan oleh Agen Perubahan untuk Mencegah Stunting, Meningkatkan Perkembangan dan IQ Anak di Kabupaten Trenggalek: Transforming Childhood: Nutrition Interventions in the First 1000 Days of Life to Prevent Stunting and Enhance IQ Children in Trenggalek - Pudjirahaju, Astutik; Soelistyorini, Dwie; Mustafa, Annasari; Kristianto, Yohanes (Amerta Nutrition, 2025)
Background: The prevalence of stunting in Trenggalek Regency is high, i.e. 38.63%. This problem occurred in ten villages from various sub-districts and affected over 500 children. Various intervention methods have been implemented to address stunting, but the education for midwives and posyandu cadres as agents of change remains relatively uncommon. Objectives: To assess the impact of specific nutritional interventions carried out by cadres and village midwives on the prevalence of stunting, child development (behavioral, mental, and psychomotor), and Intelligence Quotient (IQ) of children over 24 months in Trenggalek. Methods: The research used a quasi-experiment design with a pre-test – post-test approach. Specific nutrition interventions were provided to the agents through nutrition education and training based on balanced nutrition guidelines and breastfeeding counseling from the World Health Organization (WHO). Assistance was also provided to pregnant women during their first trimester. The collected data included the growth, development, and IQ of children aged 0-24 months. Results: The nutrition knowledge of the agent improved after the intervention, with an average score of 63.0±16.2 before the intervention and 76.8±14.7 after. The prevalence of stunting in selected health centers has decreased to 7.5%. This contributes to achieving a low stunting "green" status for the regency. Conclusions: This study shows that increasing the knowledge of change agents can effectively reduce stunting. Stunting prevention can be achieved through proper maternal and childcare practices, including early initiation of breastfeeding, exclusive breastfeeding, appropriate complementary feeding, and complete immunization.